Mechanical properties of recycled PP reinforced with microcrystalline cellulose: effect of MAPP content - Samat, Noorasikin; Zulkifli, Nur Izzati; Anuar, Hazleen (2013)
The effect of different amounts of maleic anhydride grafted polypropylene (MAPP) coupling agent (2, 3 and 5 wt%) on mechanical properties of recycled polypropylene/microcrystalline cellulose (rPP/MCC) composites was determined. 4 wt% of MCC was compounded with rPP via melt mixing method followed by injection molding. The mechanical properties of the composites were characterized by tensile and dynamic mechanical analysis (DMA) tests. It was found that at low filler content, different amounts of MAPP resulted in no appreciable change in tensile strength and modulus. Nevertheless, the DMA result exhibited that the composite with 3 wt% of MAPP shows the highest value and temperature in storage modulus and loss tangent, respectively. This result indicates that a strong interaction between MCC and rPP occurred at this specific MAPP amount which also affects the rigidity and thermal property of the composites. It is presumed that the 3 wt% of MAPP will also influence the mechanical and thermal properties of rPP composites at higher content of MCC.